On captorhinids : analysis of morphological characters with particular attention to skull sculpturing - Correia, Joana Isabel de Órfão (2021)
Captorhinids are an extinct group of Palaeozoic eureptiles, being model representatives of basal Reptilia. These non-synapsid amniotes represent the first major radiation of terrestrial vertebrates. They have a conservative skull anatomy with the presence of conspicuous skull sculpturing. Morphological skull features are extensively used in phylogenetic analysis, particularly external cranial bone surface texture (skull sculpturing). However, in captorhinids there is no consensus on the definition and classification of this trait, and different authors use different words to describe similar character states. In addition, current technology provides new information from previously undescribed structures in bone texture that require proper nomenclature definition in order to be used in phylogenetic analyses. Here we present a deep redescription of all captorhinid phylogenetic characters used in recent literature. All characters and character states and figured in a visual portfolio to be used as a guide in future studies. We also propose a redefinition of skull sculpturing terminology, standardize correspondent character states, and define multiple new characters. This new data allowed to generate new phylogenetic analyses that include 23 of the captorhinomorphs species currently described. We also compare our findings with the most recent available phylogenetic data. We used image analysis software (Krita and FIJI) to isolate bone texture networks and individual polygons. The resulting data was analyzed on RStudio, where we performed statistical tests to find differences in skull sculpturing patterns. The methodology here developed can be easily applied for any other research on extant or extinct animals that also present sculpturing in their skull, bringing new light into the evolutionary history of this extremely curious evolutionary novelty.